Medieval warfare : a history - Keen, Maurice Hugh (Oxford University Press, 1999)
Written by 12 scholars, this richly illustrated volume illuminates the medieval period, examining over 700 years of European conflict from the time of Charlemagne to the end of the Middle Ages (1500). 100 illustrations. The medieval period was a singular epoch in military history-an age profoundly influenced by martial ideals, whose very structure of society was organized for war, and whose leaders were by necessity warriors. Now, the richly illustrated Medieval Warfare illuminates this era, examining over seven hundred years of European conflict, from the time of Charlemagne to the end of the middle ages (1500). Twelve scholars examine medieval warfare in two sections. The first section explores the experience of war chronologically, with essays on the Viking age, on the wars and expansion of the eleventh and twelfth centuries, on the Crusades, and on the great Hundred Years War between England and France. The second section traces developments in the art of warfare: fortification and siege craft, the role of armored cavalrymen, the use of mercenary forces, the birth of gunpowder artillery, and the new skills in navigation and shipbuilding.